MANAJEMEN KEGIATAN EKSTRAKURIKULER DALAM MENINGKATKAN KUALITAS SEKOLAH DI MTS BORO KABUPATEN JENEPONTO - Suarga; Sukmawati (Department of Islamic Education Management, 2023)
The purpose of this study was to determine the management of extracurricular activities in improving the quality of schools at MTs Boro. Activities that include several management functions, namely planning, organizing, implementing, monitoring and evaluating extracurricular activities. The type of research used in this research is qualitative with a descriptive research type approach. The method of data collection was done by interviewing the Head of Madrasah, Deputy Head of Madrasah for Student Affairs, 5 teachers who coached extracurricular activities and 6 students and documentation. Sources of data used are primary and secondary data. Then the techniques of data management and data analysis were carried out through data reduction, data presentation and drawing conclusions. The results of this study indicate that the management of extracurricular activities in improving the quality of schools at MTs Boro, Jeneponto Regency includes 5 management functions. Planning for extracurricular activities at MTs Boro is carried out through a work meeting at the beginning of the new school year which is usually held in July. The matters discussed included determining the types of extracurricular activities and their objectives, determining the person in charge of activities, guidelines for implementing activities, schedules for extracurricular activities, facilities and infrastructure needed in order to improve the quality of schools in triggering the interest of new students, as for extracurricular activities in MTs Boro is scouting activities, religious activities, sports activities, PMR activities, arts and sispala activities. The organization carried out at MTs Boro is the selection of extracurricular coaches, namely teachers who are considered to have the potential to foster students in extracurricular activities. The structure in extracurricular activities at MTs Boro consists of the Head of Madrasah, Deputy Head of Madrasah for Student Affairs, and teachers who guide extracurricular activities. The implementation of extracurricular activities at MTs Boro is carried out outside of learning hours according to a predetermined schedule and is accompanied by an extracurricular activity coach. scouting activities, religious activities, sports activities, PMR activities, arts activities and sispala Supervision is held to determine the level of success in achieving the desired achievement. The evaluation is carried out at the end of the semester, while the things that are evaluated are facilities and infrastructure, the number of meetings that must be met in one semester and the smooth implementation of extracurricular activities. The implications of this study: (1) In order to carry out extracurricular activities effectively, it is expected that schools will complete infrastructure facilities that support the improvement of better school quality. (2) In order to maximize efforts in developing students' talents, it is necessary to carry out regular extracurricular activities.